Social work and foster care - Brown, Helen Cosis (Post-qualifying social work practice., 2014)
Working with children in foster care is a demanding and rigorous aspect of social work practice. Often difficult decisions have to be made and for students and practitioners alike, there is a vast array of legislation, law and social policy to understand. This book will help social workers and social work students get to grips with the complexity of foster care. The child is placed at the heart of the text and there are substantial chapters on law, policy frameworks and the overreaching theoretical and research evidence to support good practice.